STRATEGI POLITIK DWI AJENG SEKAR RESPATY DALAM PEMILIHAN LEGISLATIF DPD RI DI KOTA BATAM TAHUN 2024 - Siregar, Caroline Kezia; Nisaa, Fadhiilatun (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
In 2024, simultaneous elections will be held, including for the Regional Representative Council (DPD RI). In that election, Dwi Ajeng Sekar Respaty ran as a candidate for the DPD RI and was the only female candidate, and Sekar successfully won. During the election process, Sekar employed strategies to achieve victory. As a young woman, Sekar needed to use strong strategies to secure enough votes to be elected. Therefore, this study is conducted to examine the political strategies of Dwi Ajeng Sekar Respaty in the DPD RI legislative elections in Batam City in 2024. This study aims to determine the winning strategy of Dwi Ajeng Sekar Respaty in the 2024 DPD RI legislative election in Batam City. This research uses a qualitative research method with a type of descriptive qualitative research. The theory used for this research is based on Peter Schroder's theory, with indicators of offensive and defensive strategies. The results of this study are that Dwi Ajeng Sekar Respaty managed to get 111,920 votes and was successfully elected as a member of the DPD RI. This success was thanks to the strategy carried out, an offensive strategy in the form of issue mapping and social research used to group social conditions and local issues so that they can be used as the main campaign material, then strengthening self-image by creating an interesting political narrative through self-branding as a young woman who cares about gender equality and narrating in the vision and mission, Sekar also carried out a strategy to expand support by approaching community groups from across religions and ethnicities, then Sekar carried out a strategy by approaching political marketing. The second strategy, namely a defensive strategy by utilizing the big name of Soerya Respationo or Romo who is the father of Dwi Ajeng Sekar Respaty. Soerya is an influential person in the Riau Islands with his track record, besides that Soerya is also close to many community groups which is an opportunity for Sekar to secure his vote. Keywords: DPD, Legislative Elections, Political Strategy